Suicidality among older Australian adults - Klein, Britt; Shandley, Kerrie; McLaren, Suzanne; Clinnick, Lisa; Nguyen, Huy Van (Frontiers in Public Health, 2023)
Background: Vulnerability to suicidality is a concern among older adults, particularly as this proportion of the population is growing. Determining what factors contribute to suicidality will help to create a framework for understanding and assessing suicidal risk among older adults and developing effective treatments. This study examined suicidality among older Australian adults. Method: This study forms part of a larger study to trial a survey to collect cross-sectional data on the mental and physical health of older Australian adults across time. One hundred and fourteen Australian residents aged 65 years and over completed an anonymous survey online or by returning a paper-and-pencil version of the survey by post. The survey took approximately 25 minutes to complete and comprised of (1) sociodemographic questions (e.g., age, gender, education), (2) validated questionnaires measuring depression, general anxiety, psychological distress, insomnia, substance dependence, problem gambling, and stress, and (3) mental health and physical wellbeing items (e.g., religiosity, assistance with daily tasks, and mental health service usage in the last 12-months). The dependent variable, suicidality, was measured by asking participants whether they had ever seriously thought about committing suicide. Results: Associations with suicidality were analyzed using Chi-squares and independent samples t-tests. The results found suicidality to be significantly associated with lower levels of satisfaction with the frequency of seeing and/or communicating with friends, and inadequate levels of community engagement. Conclusion: The results of this survey reinforce the importance of social connectedness as a central and significant protective factor against suicidality among older adults.